VSP-2 attenuates secretion of inflammatory cytokines induced by LPS in BV2 cells by mediating the PPARγ/NF-κB signaling pathway - Cui Jingxin; Xu Liwei; Sun Yimeng; Dai Lingfei; Mo Yuxiu; Yun Keli; Chen Yifei; Chen Linglin (Open Life Sciences, 2024)
Neuroinflammation, characterized by microglial activation and the subsequent secretion of inflammatory cytokines, plays a pivotal role in neurodegenerative diseases and brain injuries, often leading to neuronal damage and death. Alleviating neuroinflammation has thus emerged as a promising strategy to protect neurons and ameliorate neurodegenerative disorders. While peroxisome proliferator-activated receptor gamma (PPARγ) agonists have demonstrated potential therapeutic actions on neuroinflammation, their prolonged use, such as with rosiglitazone, can lead to cardiac risks and lipid differentiation disorders. In this study, we investigated the effects of a newly synthesized PPARγ agonist, VSP-2, on secretion of inflammatory cytokines in BV2 cells. Treatment with VSP-2 significantly reduced the mRNA and protein levels of proinflammatory cytokines such as interleukin-1β (IL-1β), IL-6, and tumor necrosis factor-α (TNF-α). Furthermore, VSP-2 attenuated the phosphorylation of nuclear factor kappa B (NF-κB) (65 kD) and IκBα, as well as the nuclear translocation of NF-κB (65 kD). Additionally, the use of PPARγ small interfering RNA was able to attenuate the effects of VSP-2 on proinflammatory cytokines and the NF-κB pathway. In conclusion, our findings suggest that VSP-2 effectively suppressed the expressions of IL-1β, IL-6, and TNF-α via the PPARγ/NF-κB signaling pathway. Given its potential therapeutic benefits, VSP-2 may emerge as a promising candidate for the treatment of neurodegenerative diseases or brain injuries associated with neuroinflammation.